REKAYASA PERANGKAT LUNAK SISTEM INFORMASI GEOGRAFIS (SIG) TATA LETAK PENYEDIA SARANA PENANGGULANGAN KEBAKARAN (Jurnal Sistem Informasi dan Informatika (Simika), 2019)
The fire department is a government agency that handles fire and fire prevention. After conducting research, quite a lot of activities or activities found in the fire department, especially in the field of fire prevention, one of which is managing data about the layout of providers of fire prevention facilities so that they can be useful information and help in fire prevention efforts by postal officers extinguisher. But in doing so, fire department officials find difficulties such as the difficulty of finding the location of the supporting aspects, misinformation of the layout of supporting facilities so that it takes a lot of time, and demographic data has not been thoroughly integrated and centralized with the main database. making it difficult to update and allow errors. Geographical Information System (GIS) layout of providers of web-based fire prevention facilities is expected to provide solutions to the problems above, thus facilitating the process of managing information on the layout of providers of fire prevention facilities